APPLICATION OF PROJECT-BASED MODELS IN FINE ARTS LEARNING THROUGH CLASS EXHIBITIONS AS A PLACE FOR CREATIVE PROCESSES AND ART APPRECIATION AT UNIVERSITY - Asmarani, Ratih; Mariati, Pance (Universitas Nahdatul Ulama Surabaya, 2021)
Abstract: Fine arts education courses are Science and Skills Subjects contained in the curriculum structure of the Elementary School Teacher Education Study Program at Hasyim Asy'ari University, Jombang. This course has learning outcomes, namely students have awareness of local culture and environmental-based creative competencies to be applied in learning in elementary schools (SD). Therefore, a container is needed as a creative process and appreciation of works through art exhibition activities. This research method is qualitative as well as primary and secondary data collection through observation of the implementation of art learning. The purpose of this research is to produce works of art to be appreciated through class exhibitions as a forum for the creative process and art appreciation. It is proven by this activity being able to provide experience in the process of creating fine arts using various themes, materials and dimensions for the development of student creativity aspects as well as training students to appreciate traditional and contemporary cultural works. In the implementation of learning, learning models are needed to achieve high quality learning. learning models help educators to package a lesson that can attract interest in appreciating and creating works of art. Keywords: exhibitions, fine arts, creative processes, appreciation Abstrak: Mata kuliah pendidikan seni rupa merupakan Mata Kuliah Keilmuan dan Ketrampilan yang terdapat dalam struktur kurikulum Prodi Pendidikan Guru Sekolah Dasar di Universitas Hasyim Asy’ari Jombang. Mata kuliah ini memiliki capaian pembelajaran yaitu mahasiswa memiliki kesadaran terhadap budaya lokal dan kompetensi kreatif berbasislingkungan untuk diaplikasikan dalam pembelajaran di Sekolah Dasar (SD). Oleh karena itu, dibutuhkan wadah sebagai proses kreatif dan apresiasi karya melalui kegiatan pameran seni rupa. Metode penelitian ini adalah kualitatif serta pengumpulan data primer dan sekunder melalui observasi terhadap pelaksanaan pembelajaran seni rupa. Tujuan penelitian ini adalah untuk memproduksi karya seni rupa untuk diapresiasi melalui pameran kelas sebagai wadah proses kreatif dan apresiasi seni. Terbukti dengan adanya kegiatan ini mampu memberikan pengalaman proses berkarya seni rupa dengan menggunakan berbagai tema, material dan dimensi untuk pengembangan aspek kreativitas mahasiswa serta melatih mahasiswa untuk menghargai karya budaya tradisional maupun kontemporer.Dalam pelaksanaan pembelajaran dibutuhkan model pembelajaran guna tercapainya kualitas pembelajaran yang tinggi.Pengembangan model pembelajaran membantu pendidik untuk mengemas sebuah pembelajaran yang dapat menarik minat dalam mengapresiasi dan berkreasi karya seni rupa.Penelitian ini menghasilkan acuan berupa model pembelajaran berbasis proyek yang berorientasi pada kecerdasan interpersonal dan aplikasinya dalam pemebelajaran seni rupa. . Kunci: pameran, seni rupa, proses kreatif, apresiasi